Virtual-assisted lung mapping in sublobar resection of small pulmonary nodules, long-term results. (18th October 2021) - Yamaguchi, Hirokazu; Sato, Masaaki; Yamamoto, Kazumichi; Ueda, Keiko; Date, Hiroshi; Chen-Yoshikawa, Toyofumi; Yamada, Yoshito; Tokuno, Junko; Yanagiya, Masahiro; Kojima, Fumitsugu; Yoshiyasu, Nobuyuki; Kobayashi, Masashi; et al.
Abstract: OBJECTIVES: The short-term efficacy of virtual-assisted lung mapping (VAL-MAP), a preoperative bronchoscopic multi-spot lung-marking technique, has been confirmed in 2 prospective multicentre studies. The objectives of this study were to analyse the local recurrence and survival of patients enrolled in these studies, long-term. METHODS: Of the 663 patients enrolled in the 2 studies, 559 patients' follow-up data were collected. After excluding those who did not undergo VAL-MAP, whose resection was not for curative intent, who underwent concurrent resection without VAL-MAP, or who eventually underwent lobectomy instead of sublobar resection (i.e. wedge resection or segmentectomy), 422 patients were further analysed. RESULTS: Among 264 patients with primary lung cancer, the 5-year local recurrence-free rate was 98.4%, and the 5-year overall survival (OS) rate was 94.5%. Limited to stage IA2 or less (≤2 cm in diameter; n  = 238, 90.1%), the 5-year local recurrence-free and OS rates were 98.7% and 94.8%, respectively. Among 102 patients with metastatic lung tumours, the 5-year local recurrence-free rate was 93.8% and the 5-year OS rate was 81.8%. Limited to the most common (colorectal) cancer ( n  = 53), the 5-year local recurrence-free and OS rates were 94.9% and 82.3%, respectively. CONCLUSIONS: VAL-MAP, which is beneficial in localizing small barely palpable pulmonary lesions and determining the appropriate resection lines, was associated with reasonable long-term outcomes. Subj collection: 152, 1542 Abstract : Suspicious small pulmonary nodules are being found more often, with the development and widespread use of high-resolution computed tomography (CT).